Mengkaji Alur Cerita dalam Novel Ally Karya Arleena - Katharina Woli Namang; Yeremias Bardi; Maria Palma Vita (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The novel reveals Ally's life, which is not an ordinary life. Often she finds herself placed in a life that seems to belong to her, but is not. And suddenly the word "home" has a new meaning. Will Ally have the opportunity to go "home"? Will she be able to return to the love she left behind in another life? . This study aims to reveal the plot of the novel by Arleena and provide information and describe the plot in the novel Ally by Arleena. This research uses a description method. The data used in this Research are quotations in the novel Ally by Arleena. The data source in this Research is the novel Ally by Arleena. The results show that the plot of an unusual life that will make us think again about the meaning of life and the meaning of love is actually interesting.